Endophytic colonization of the nematophagous fungus Pochonia chlamydosporia in Solanaceae and Cucurbitaceae crops - Ceiro-Catasú, Wilson Geobel; Arévalo-Ortega, Jersys; Hidalgo-Díaz, Leopoldo (Agronomía Mesoamericana, 2021)
Introduction. The fungal species of the genus Pochonia are important for the management of phytoparasitic nematodes. Some of them endophyte colonize their plant hosts and provide adaptability, plant bio-stimulation, and resistance induction; these advantages are essential for the selection of strains to be used in the bio-management of phytonematodes. Objective. To evaluate the endophytic colonization and plant bio-stimulation by the nematophagous strains IMI SD 187 and 193 of P. chlamydosporia on horticultural species of the Solanaeceae and Cucurbitaceae families. Materials and methods. The experiment was carried out inside greenhouses at the National Center for Animal and Plant Health, Mayabeque province, Cuba. Two strains of P. chlamydosporia were used, named IMI SD 187 and 193, as well as cultivars of tomato (S. lycopersicum) cv. HA 3057, pepper (Capsicum annuum L.) cv. Grandisimo, cucumber (Cucumis sativus L.) cv. INIVIT P 2007, and melon (Cucumis melo L.) cv. Zest F1. In both strains, endophytic, substrate, and root colonization, as well as some plant growth parameters were evaluated. Results. The evaluated strains colonized between 3 and 16 % of the interior of the roots. The IMI SD 187 strain colonized all the evaluated species, while 193 could not colonize the melon; however, both strains colonized the root and the substrate with values between 2x103 and 2x104 CFU g-1, respectively. IMI SD 187 reached the highest bio-stimulation values in length and fresh mass of the roots in pepper. Conclusion. The two native strains of P. chlamydosporia colonized the studied species and the highest bio-stimulation of growth was obtained with IMI SD 187 in the pepper cultivar.